Analysis and Design of Parking Facilities for Nashik City - Gangurde, Pranav A.; Naktode, P. L. (AMC Indian Journal of Civil Engineering, 2019)
This paper includes the study of parking facility for Nashik city. Nashik’s vehicle use statics are increasing day by day. It is a major issue for proper parking facilities in order to maintain traffic conditions and adequate traffic flow in congested area in the city. To overcome traffic and parking problems, we need to understand parking demands, so that we can improve parking facilities. So, in order to know the parking demand, we have to first analyze parking patterns. To avoid traffic congestion, proper design of parking space is very important. With the help of pricing model which gives revenue to municipal co-operation, and with the help of parking study we need to decide provision of parking facilities like (multi-store parking, mechanical parking) which should be provided in congested areas. Parking problems in other parts of the city can be solved by using these analysis and pricing models.